2015
DOI: 10.1097/icl.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Clinical Outcomes of a Two-Step Surgical Management for Keratoconus—Topography-Guided Photorefractive Keratectomy/Cross-Linking After Intrastromal Corneal Ring Implantation

Abstract: Same-day combined TG-PRK and CXL after ISCR implantation is a safe and effective option for improving visual acuity and visual function, and it halts the progression of the keratoconus. The improvements recorded after 6 months of follow-up were maintained or improved upon 1 year after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 31 publications
0
40
0
1
Order By: Relevance
“…1). Removal of duplicates and use of the selection criteria reduced the number of articles reporting the evaluation of ICRS in keratoconus to 95 articles 8,1416,26…”
Section: Resultsmentioning
confidence: 99%
“…1). Removal of duplicates and use of the selection criteria reduced the number of articles reporting the evaluation of ICRS in keratoconus to 95 articles 8,1416,26…”
Section: Resultsmentioning
confidence: 99%
“…Several authors report an improvement in the quality of vision and possibly contact lens fit due to corneal surface regularization. [2][3][4] This technique has also been evaluated for refractive surgery, particularly for complications such as decentration or difficult revision surgery. 5 For the management of corneal scarring, topography-guided custom ablation treatment was expected to become a valuable option, combining photoablation of the fibrotic tissue and regularization of the corneal surface.…”
Section: Discussionmentioning
confidence: 99%
“…All of these studies reported significant improvement in visual acuity, refraction, and corneal shape. This triple procedure can be performed in 2-stage ICRS implantation followed by simultaneous PRK and corneal CXL [ 127 130 ] or in a three-step procedure ICRS implantation followed by corneal CXL and PRK 6 months later [ 131 , 132 ].…”
Section: Combined Proceduresmentioning
confidence: 99%